Towards a model for aerosol removal by rain scavenging: The role of physical-chemical characteristics of raindrops. (15th February 2021) - Oduber, Fernanda; Calvo, Ana Isabel; Blanco-Alegre, Carlos; Castro, Amaya; Alves, Célia; Cerqueira, Mário; Lucarelli, Franco; Nava, Silvia; Calzolai, Giulia; Martin-Villacorta, Javier; Esteves, Valdemar; Fraile, Roberto
Highlights: Linear models were built (α<0.05) to assess the efficiency of rain scavenging. A higher volume of precipitation favors the elimination of water-soluble species. The removal of water-insoluble species is favored by larger raindrop diameters. Removal coefficients are affected by airborne concentrations before precipitation. Scavenging is favored by long and continuous rains at low intensities (<0.8 mm h −1 ). Abstract: A one-year study was carried out in León, Spain, in order to characterize physically and chemically the precipitation. With the aim of studying the scavenging process of atmospheric pollutants, scavenging ratio and removal coefficients were calculated through physical parameters of raindrops (obtained by disdrometer data) and through chemical properties of aerosols. Finally, linear models for the prediction of the chemical composition of rainwater and the efficiency of the removal effect were established. In general, the rainwater was dominated by NH4 + > SO4 2− > NO3 − in all seasons. Higher ion concentrations and conductivity and lowest pH were observed in summer, due to the low volume of rain. In winter, the high values of Na + and Cl − in the rainwater showed the contribution from marine sources, while in summer the high concentrations of Ca 2+, Mg 2+, SO4 2−, NH4 + and NO3 − reflected the contribution from both crustal and anthropogenic sources. The linear models revealed that the amount of dissolved organic carbon and of the water-soluble ions in rain samples, Ca 2+, SO4 2−, NO3 −, increases with the volume swept by the falling drops. Insoluble carbon fraction has a negative dependence with the volume swept and positive with the diameter of the raindrop. Removal coefficients are affected by the concentration in the air of each species before precipitation, the duration of the event and the time elapsed between two precipitation events. Graphical abstract: Image, graphical abstract